Evolution of hierarchical porous structures in supramolecular guest–host hydrogels. Issue 37 (2nd September 2016) - Rodell, Christopher B.; Highley, Christopher B.; Chen, Minna H.; Dusaj, Neville N.; Wang, Chao; Han, Lin; Burdick, Jason A.
Abstract : Hierarchical self-assembly of supramolecular guest–host hydrogels results in porous hydrogels at the microscale with tunable properties. Abstract : Macromolecular interactions are used to form supramolecular assemblies, including through the interaction of guest–host chemical pairs. Microstructural heterogeneity has been observed within such physical hydrogels; yet, systematic investigation of the microstructure and its determining inputs are lacking. Herein, we investigated the hierarchical self-assembly of hyaluronic acid (HA) modified by the guest–host pair adamantane (Ad-HA, guest) and β-cyclodextrin (CD-HA, host), as well as with methacrylate groups to both tether fluorescent agents and to covalently stabilize the material structure. We observed microporous materials in the hydrated state, which temporally arose from initially homogenous hydrogels composed of the two polymers. Independent fluorescent labeling of Ad-HA and CD-HA demonstrated spatiotemporal co-localization, indicative of guest–host polymer condensation on the microscale. The hydrogel void fractions and pore diameters were independently tuned through incubation time (0–7 days), polymer concentration (1.25–10 wt%), and polymer modification (25–50% Ad-HA modification). Void fractions as great as 93.3 ± 2.4% were achieved and pore diameters ranged from 2.1 ± 0.5 to 1025.4 ± 209.4 μm. The segregation of discrete solid and solute phases was measured with both atomic force microscopy and diffusive microparticle tracking analysis, where the solute phase contained only dilute polymer. The study represents a systematic investigation of hierarchical self-assembly in binary associating hydrogels, and provides insights on mechanisms that control microstructure within supramolecular hydrogels.